Sustainable structural design optimization - prestressed concrete beams - Ng, Kok Hang (Nanyang Technological University, 2024)
The dynamic interaction between urban and earth systems meant that inputs made by either system often produce a cascading impact on the other. The adverse effects of climate change which is largely driven by human activities are being felt across global communities in profound manners. Imperatively, the construction sector has been identified as a major contributor to global greenhouse gas emissions. While new technologies and research have been made to reduce the carbon emissions during the operational phase, there is significant room for improvement regarding embodied carbon (EC) emissions which has become an influential contributor to global emissions.